2013
DOI: 10.1093/ntr/ntt147
|View full text |Cite
|
Sign up to set email alerts
|

Craving, Cue Reactivity, and Stimulus Control Among Early-Stage Young Smokers: Effects of Smoking Intensity and Gender

Abstract: Smoking initiation usually begins in adolescence, but how and for whom nicotine dependence emerges during this period is unclear. The cue-reactivity paradigm is well suited to examine one marker of dependence: craving-related stimulus control, i.e., the ability of environmental cues to elicit craving to smoke. This study examined the effects of both level of smoking involvement (daily vs. occasional smoking) and gender on reactivity to both smoking and alcohol cues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 56 publications
4
37
1
Order By: Relevance
“…Concerning cue reactivity, results are inconsistent. Some studies reported that women seemed more sensible to cues [33], others reported that men were [41], whereas others did not find any difference [42]. More investigations are needed on this topic.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Concerning cue reactivity, results are inconsistent. Some studies reported that women seemed more sensible to cues [33], others reported that men were [41], whereas others did not find any difference [42]. More investigations are needed on this topic.…”
Section: Discussionmentioning
confidence: 95%
“…pictures of glasses of beer or cigarette packs). For example, for alcohol cue and cravings to smoke, Carpenter et al [33] showed that daily smokers reported a higher response to alcohol visual cue rather than occasional smokers. Polydrug use has been well studied for alcohol and tobacco use [34], and we know that cigarette smoking increases during alcohol self-administration and vice versa [35].…”
Section: Discussionmentioning
confidence: 99%
“…9 Laboratory cue-reactivity studies have examined men's and women's responses to cues, with mixed results. Some studies suggest that women exhibit greater craving in response to smoking cues, 6,11,12,13 while a larger study of 207 smokers who completed over 1,000 reactivity sessions found no gender differences in cue effects on craving and smoking.…”
Section: Introductionmentioning
confidence: 99%
“…There are gender differences in reactivity to cues; for example, females express greater craving in response to smoking-related cues when compared to men (Knott et al, 2008;Tong, Bovbjerg, & Erblich, 2007). Previous research has also found that females show higher sensitivity than males to negative emotional cues (Carpenter et al, 2014;Colamussi, Bovbjerg, & Erblich, 2007;Saladin et al, 2012;Wray et al, 2015). There are other factors that have been related to greater craving for cigarettes, including younger age, higher nicotine dependence and symptoms of anxiety (García-Rodríguez et al, 2011;Sayette, Martin, Wertz, Shiffman, & Perrott, 2001;ThompsonLake et al, 2014;Watson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%